Printno. 8027 - 4696(4). Poster probably published in late sixties or early seventies. See also BG E13/122-3 and BG E12/174
Printno. 8027 - 4696(4). Poster probably published in late sixties or early seventies. See also BG E13/122-3 and BG E12/174.